The Role of Local Government in the Development of SMEs - An Analysis of the Instruments of Entrepreneurship Support on the Example of Lodz - Aleksandra MŁOCZKOWSKA (Communications of International Proceedings, 2025)
The purpose of the article is to analyze the role of local government units in shaping the conditions for the development of micro, small and medium-sized enterprises (SMEs) on the example of the city of Lodz. The article is based on a literature review, analysis of strategic documents and selected projects and foundational data. It also includes references to the results of empirical research on the relationship between entrepreneurs and city authorities. Conclusions indicate the need for closer cooperation between the local government and the SME sector and the implementation of better coordinated and more accessible support instruments.
Keywords: local government; SMEs; support instruments; local development; Lodz; economic policy; social media